2004
DOI: 10.4315/0362-028x-67.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Escherichia coli O157:H7, Listeria monocytogenes, and Salmonella in Two Geographically Distant Commercial Beef Processing Plants in the United States

Abstract: For two large beef processing plants, one located in the southern United States (plant A) and one located in the northern United States (plant B), prevalence of Escherichia coli O157:H7, Listeria spp., Listeria monocytogenes, and Salmonella was determined for hide, carcass, and facility environmental samples over the course of 5 months. The prevalence of E. coli O157: H7 (68.1 versus 55.9%) and Salmonella (91.8 versus 50.3%) was higher (P , 0.05), and the prevalence of Listeria spp. (37.7 versus 75.5%) and L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 30 publications
3
76
2
4
Order By: Relevance
“…These results are alarming, as several authors have shown in their studies a total absence of Salmonella on the surface of carcasses. 24,[32][33][34][35][36] Nevertheless, of the differences in the prevalence of pathogenic bacteria between this study and the aforementioned ones may be due to differences in methods, sample sizes, frequency and time of collection, transportation and storage samples, sampling seasons and age of the animals.…”
Section: Resultsmentioning
confidence: 81%
“…These results are alarming, as several authors have shown in their studies a total absence of Salmonella on the surface of carcasses. 24,[32][33][34][35][36] Nevertheless, of the differences in the prevalence of pathogenic bacteria between this study and the aforementioned ones may be due to differences in methods, sample sizes, frequency and time of collection, transportation and storage samples, sampling seasons and age of the animals.…”
Section: Resultsmentioning
confidence: 81%
“…According to a literature survey carried out by Rhoades et al (2009), the mean prevalence of L. monocytogenes on hides was 12% (10-13%). Hide data may be an indication of the regional prevalence, as different results have been found for two distantly located beef processing plants (0.8 versus 18.7%) (Rivera-Betancourt et al, 2004). Low rates of contamination of pre-evisceration carcasses reported for the same two plants (0.0 versus 1.1%) are more likely related to their harvest practices and procedures (Rivera-Betancourt et al, 2004).…”
Section: Beefmentioning
confidence: 98%
“…It has also been shown that some pathogenic bacteria, including VTEC and Salmonella, can be transferred from hides to carcasses during processing (Elder et al 2000, Reid et al 2003, Hussein and Bollinger 2005. The prevalence of pathogens in cattle identified during the slaughter process has varied considerably in the previously described surveys (Bell 1997, Scanga et al 2000, Madden et al 2001, Barkocy-Gallagher et al 2003, Rivera-Betancourt et al 2004, Brichta-Harhay et al 2008, Bosilevac et al 2009. The number of positive samples strongly depends on sampling strategies, time of the year, and the laboratory methods used during the studies.…”
Section: Discussionmentioning
confidence: 99%
“…in beef processing plants have been performed by Rivera-Betancourt et al (2004). A total of 1,032 bovine hides and the same number of corresponding carcasses were tested.…”
Section: Discussionmentioning
confidence: 99%